An Effective Health Care System through Health Technology Assessment and Evidence Based Payment System in India - Arya Kumar; Rajni Mathur; T Shirmila; Rahul More; Ravindra Kaikini; Kuldeep Bhalerao (ACHSM, 2023)
The purpose of this research is to discuss the significance of health care insurance compensation for obtaining comprehensive medical treatment in India. Through a systematic review survey focusing on the keywords like out-of-pocket, Health Technology Assessment and Health care system was conducted by using the searches from Google Scholar, Science Direct, PubMed and ProQuest Database, it is observed that India ranks among the greatest out-of-pocket (OOP) healthcare expenditures in the globe. This seems to be notwithstanding the deployment of several public health plans and the provision of a significant variety of both private and public health coverage schemes. Decrease in the treatment quality across many healthcare institutions of government is a key cause causing the typical Indian individual to constantly rely on medical services provided by private firms, heading up OOP expenses. Among the most significant problems in implementing universal health care (UHC) in India is a poor acceptance of insurance products and awareness between many Indians. The burden of large OOP expenditures on people might be lessened by increasing medical insurance acceptance, which may be accomplished by enhancing India's medical claims system.